2016
DOI: 10.1016/j.athoracsur.2016.02.013
|View full text |Cite
|
Sign up to set email alerts
|

An Extended Role of Continuous Flow Device in Pediatric Mechanical Circulatory Support

Abstract: The third-generation, continuous flow device can provide durable support in the pediatric population. The selection strategy for patients who benefit most from the device continues to evolve. It is anticipated that a smaller design in the future will benefit an even wider pediatric population with heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…Although not without risk, pediatric VAD support is successful in bridging children, primarily noninfants with DCM, to HT . Because much of the risk of adverse events and mortality is early after VAD placement and largely reflective of the severity of illness prior to VAD placement, once on successful VAD support most children are neither “too sick” nor unable to wait extended durations for transplantation . The most attractive group in which to apply a time‐limited status 1A window are outpatients, well supported by continuous‐flow, intracorporeal VADs (eg, Heartmate II/III, Heartware HVAD).…”
Section: Discussionmentioning
confidence: 99%
“…Although not without risk, pediatric VAD support is successful in bridging children, primarily noninfants with DCM, to HT . Because much of the risk of adverse events and mortality is early after VAD placement and largely reflective of the severity of illness prior to VAD placement, once on successful VAD support most children are neither “too sick” nor unable to wait extended durations for transplantation . The most attractive group in which to apply a time‐limited status 1A window are outpatients, well supported by continuous‐flow, intracorporeal VADs (eg, Heartmate II/III, Heartware HVAD).…”
Section: Discussionmentioning
confidence: 99%
“…16 Peng et al . 17 series of 12 patients were 3.7–17 years, three < 5 years, all but one of whom had cardiomyopathy. Anticoagulation was begun 24 hours after implantation and only when surgical bleeding was <1 ml/kg/hour for three consecutive hours.…”
Section: Discussionmentioning
confidence: 99%
“…Two patients experienced device thrombosis but no neurologic events, two patients required mediastinal reexploration for bleeding and clot removal, and two patients developed ischemic bowel, with one death. 17 The mechanical features and intrathoracic placement of the HVAD are potentially advantageous in terms of reducing thromboembolic complications. However, the Berlin patients reported in this paper included a broad range of patient sizes and a larger proportion of both congenital cardiac disease and infectious diagnoses, which may impact SAEs and outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent multi-institutional study, we have demonstrated the feasibility of discharging majority of children on HVAD support, who may then go on to resume regular activities 33. However, recent studies (including the PediMACS registry data) show that about half of the patients supported by continuous-flow VADs are still managed in hospital 3436. As the experience with continuous-flow VAD in children advances, the home discharge rate will steadily increase.…”
Section: Current Challengesmentioning
confidence: 99%